2004
DOI: 10.1590/s0004-282x2004000200028
|View full text |Cite
|
Sign up to set email alerts
|

Whipple's disease with neurological manifestions: case report

Abstract: -Whipple´s disease (WD) is an uncommon multisystem condition caused by the bacillus Tropheryma whipplei. Central nervous system involvement is a classical feature of the disease observed in 20 to 40% of the patients. We report the case of a 62 yeards old man with WD that developed neurological manifestations during its course, and discuss the most usual signs and symptoms focusing on recent diagnostic criteria and novel treatment regimens.KEY WORDS: Whipple´s disease, inflammatory bowel disease, dementia, poly… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
4
0

Year Published

2006
2006
2020
2020

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(4 citation statements)
references
References 23 publications
0
4
0
Order By: Relevance
“…OMM and OFSM are now considered virtually pathognomonic for CNS‐WhD, and although it was stated in a single publication that these can be seen in rare cases of “oculopontocerebellar atrophy,” there is no clear evidence that OMM/OFSM occurs in disorders other than CNS‐WhD . However, OMM and OFSM are uncommon manifestations of WhD, occurring in only 8% to 20% of all CNS‐WhD cases and in 24% of those with MDs analyzed here.…”
Section: Discussion On Terminology: Myorhythmia and Myoclonusmentioning
confidence: 72%
See 2 more Smart Citations
“…OMM and OFSM are now considered virtually pathognomonic for CNS‐WhD, and although it was stated in a single publication that these can be seen in rare cases of “oculopontocerebellar atrophy,” there is no clear evidence that OMM/OFSM occurs in disorders other than CNS‐WhD . However, OMM and OFSM are uncommon manifestations of WhD, occurring in only 8% to 20% of all CNS‐WhD cases and in 24% of those with MDs analyzed here.…”
Section: Discussion On Terminology: Myorhythmia and Myoclonusmentioning
confidence: 72%
“…Whipple's disease (WhD) is a rare but treatable infectious disease from Tropheryma whipplei (TW), with an estimated incidence of 0.4 to 1.0 per 1,000,000 a year . The brain follows the gastrointestinal tract as the second major site of involvement, with CNS involvement on postmortem found in up to 50% of cases, most frequently in a periventricular and periaqueductal distribution . The percentage of clinical CNS involvement varies considerably, ranging from 6% to 63%, with most estimates of 10%‐43%.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Symptoms associated with Whipple's disease range from abnormal movements (myoclonus, choreiform movements, oculomasticatory myorhythmia), hypersomnia, coma, ophthalmoplegia, cognitive impairment, frontal lobe syndrome, cerebellar ataxia, or upper motor neuron and extrapyramidal symptoms (127). It has even been suggested that there is a relation between T. whipplei infection and the development of Parkinson's disease (117,128,129), but it is unlikely that there is a causative relation. Although most Whipple's disease patients do not present any obvious neurological symptoms, postmortem investigation showed that 90% of brain and spinal cord specimens from both patients and presumed carriers revealed lesions of the CNS, meaning that CNS involvement is more common than expected from the clinical manifestations (33).…”
Section: Classic Whipple's Diseasementioning
confidence: 99%